2020
DOI: 10.3390/nu12030608
|View full text |Cite
|
Sign up to set email alerts
|

To Eat or Not to eat: A Review of the Relationship between Chocolate and Migraines

Abstract: Migraine is a chronic disorder with episodic attacks, and patients with a migraine often report that certain factors can trigger their headache, with chocolate being the most popular type of food-based trigger. Many studies have suggested a link between chocolate and headaches; however, the underlying physiological mechanisms are unclear. As premonitory symptoms may herald migraine attacks, a question arises regarding whether eating chocolate before a headache is a consequence of a food craving or indeed a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 76 publications
1
23
0
4
Order By: Relevance
“…1 Interestingly, chocolate has been a matter of investigation as one of the migraine triggers. 131 A recent systematic review 132 has looked into 25 studies that evaluated if chocolate acts as a trigger in migraine, where 23 studies reported that chocolate could trigger migraine. There were also three provocative studies [133][134][135] that tested the triggering effect of chocolate compared with placebo, and neither of those could identify a significant outcome.…”
Section: Dietary Consistency and Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…1 Interestingly, chocolate has been a matter of investigation as one of the migraine triggers. 131 A recent systematic review 132 has looked into 25 studies that evaluated if chocolate acts as a trigger in migraine, where 23 studies reported that chocolate could trigger migraine. There were also three provocative studies [133][134][135] that tested the triggering effect of chocolate compared with placebo, and neither of those could identify a significant outcome.…”
Section: Dietary Consistency and Migrainementioning
confidence: 99%
“…Therefore, based on these findings, the authors of the systematic review concluded that evidence is still lacking to draw any recommendation for migraine patients about eating or avoiding chocolate. 132 Neurotransmitter, hormone, and adipocytokine levels in migraine patients are different compared with controls that might also influence the desire for food, or food intake or even the metabolic control of the hypothalamus 18,136 in affected patients. For example, orexin A, was elevated in headache phase, 32 while serotonin levels were lower during the interictal phase.…”
Section: Dietary Consistency and Migrainementioning
confidence: 99%
“…Evaluating the role of diet in migraine is complex because multiple triggers and variables can modify the pain threshold in an individual, and this factor is frequently neglected in favor of preventive drug therapy for pediatric patients [ 75 ]. Although chocolate is the most frequent dietary trigger for migraines in children [ 23 , 74 ], a recent review article found insufficient evidence of chocolate being described as a definitive migraine trigger [ 76 ].…”
Section: Prevalence Of Trigger Factors In Migrainementioning
confidence: 99%
“…However, there is a lack of scientific evidence to support these diets as a therapeutic recommendation [ 75 ]. Even chocolate lacks sufficient evidence of being labeled a proper trigger, as per a recent systematic review [ 76 ]. Certain dietary interventions may improve clinical outcomes in some individuals with migraines; these associations need to be confirmed by high-quality longitudinal studies [ 75 ].…”
Section: Prevalence Of Trigger Factors In Migrainementioning
confidence: 99%
“… 20 According to the recent studies on single food items or nutrients, red wine, caffeine, chocolate, and monosodium glutamate (MSG) were among the most consistent food triggers of migraine. 21 - 24 Moreover, the effect of different diets, including gluten-free diets, 25 immunoglobulin G (IgG) elimination diets, 26 Dietary Approaches to Stop Hypertension (DASH) diet, 27 low-fat diets, 28 low-glycemic diets, 29 diets containing high omega-3 and low omega-6 fatty acids, 30 and ketogenic diets 31 have been studied on migraine headache. Despite some promising results, currently there is no specific “migraine diet” due to inconsistency between studies.…”
Section: Introductionmentioning
confidence: 99%